2016
DOI: 10.1080/16506073.2016.1191083
|View full text |Cite
|
Sign up to set email alerts
|

Self-help interventions for adjustment disorder problems: a randomized waiting-list controlled study in a sample of burglary victims

Abstract: Adjustment disorders (AjD) are among the most frequent mental disorders yet often remain untreated. The high prevalence, comparatively mild symptom impairment, and transient nature make AjD a promising target for low-threshold self-help interventions. Bibliotherapy represents a potential treatment for AjD problems. This study investigates the effectiveness of a cognitive behavioral self-help manual specifically directed at alleviating AjD symptoms in a homogenous sample of burglary victims. Participants with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 63 publications
(70 reference statements)
1
31
0
3
Order By: Relevance
“…The stressor list of the ADNM was used in nine reviewed studies. However, the number of stressors in the first part of the ADNM ranged considerably across different studies: 10 stressors (Bachem & Maercker, 2016; Bachem, Perkonigg, Stein, & Maercker, 2016), 13 stressors (Horn & Maercker, 2016), 15 stressors (Zelviene, Kazlauskas, Eimontas, & Maercker, 2017), 16 stressors (Glaesmer, Romppel, Brähler, Hinz, & Maercker, 2015), 17 stressors (Eimontas et al, 2017), and 19 stressors (Lorenz, Bachem, & Maercker, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The stressor list of the ADNM was used in nine reviewed studies. However, the number of stressors in the first part of the ADNM ranged considerably across different studies: 10 stressors (Bachem & Maercker, 2016; Bachem, Perkonigg, Stein, & Maercker, 2016), 13 stressors (Horn & Maercker, 2016), 15 stressors (Zelviene, Kazlauskas, Eimontas, & Maercker, 2017), 16 stressors (Glaesmer, Romppel, Brähler, Hinz, & Maercker, 2015), 17 stressors (Eimontas et al, 2017), and 19 stressors (Lorenz, Bachem, & Maercker, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported outcomes of cognitive behavioural (CBT) self-help interventions for ICD-11 AjD (Bachem & Maercker, 2016; Kazlauskas, Zelviene, & Eimontas, 2017; Maercker et al, 2015). One of the reviewed studies included a sample of patients in psychopharmacological treatment (Bachem et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations